Decreased gastrostomy tube incidence and weight loss after transoral robotic surgery for low‐ to intermediate‐risk oropharyngeal squamous cell carcinoma. Issue 11 (13th August 2018) - Heah, Harold; Goepfert, Ryan P.; Hutcheson, Katherine A.; Garden, Adam S.; Gunn, G. Brandon; Fuller, Clifton D.; Lewin, Jan S.; Kupferman, Michael E.; Holsinger, F. Christopher; Hessel, Amy C.; Gross, Neil D.
Abstract: Background: Functional outcomes after treatment for oropharyngeal squamous cell carcinoma (SCC) are increasingly prioritized. The purpose of this study was to investigate the incidence of gastrostomy tube placement and weight loss in patients with oropharyngeal SCC who may be eligible for either transoral robotic surgery (TORS) or nonsurgical management. Methods: We conducted a retrospective review of previously untreated T1 to T2 and N0 to N2b oropharyngeal SCC to determine the rates of gastrostomy tube placement and weight loss according to Common Terminology Criteria for Adverse Events (CTCAE) criteria. Multivariate regression models were fit to compare these end points between groups. Results: Two hundred twenty‐three patients were included, comprised of 66 patients who underwent TORS and 157 patients who underwent (chemo)radiation. Thirty‐two (48.5%) of the TORS patients received adjuvant radiation. On multivariate analysis, patients treated nonsurgically were 10.6 times and 8.1 times more likely to receive a gastrostomy tube and experience greater than CTCAE grade 1 weight loss, respectively. Conclusion: In selected patients with oropharyngeal SCC, TORS may help avoid critical weight loss and gastrostomy tube placement in the acute treatment period.